Combinatorial and functional approach of solving matrices under given restrictions. (2021) - Kumar, Pravesh; Shrivastava, Ritu; Bhardwaj, Ramakant; Sharma, Raghavendra; Mishra, Jyoti
Abstract: In the work, with the broad range of application of matrices using combinatorics, efforts are made to add something new and interesting concepts in applications of matrices. Few methods s are given related to a matrix having n elements, where n is a non-prime naturals. This proposed technique will be useful for all types of aspirants appearing in any examination that contains matrices & determinants, combinations in their syllabus. The proposed techniques will add a new feather to the crown of their studies/preparation. The goal of this study is to develop a unique model that could locate these unique techniques without doing much calculation, thus saving time and increasing chance of success. Obtained results are very useful to solve special type of methods which are used in materials researches.